2004
DOI: 10.4315/0362-028x-67.2.328
|View full text |Cite
|
Sign up to set email alerts
|

Tracking of Listeria monocytogenes in Smoked Fish Processing Plants

Abstract: Four smoked fish processing plants were used as a model system to characterize Listeria monocytogenes contamination patterns in ready-to-eat food production environments. Each of the four plants was sampled monthly for approximately 1 year. At each sampling, four to six raw fish and four to six finished product samples were collected from corresponding lots. In addition, 12 to 14 environmental sponge samples were collected several hours after the start of production at sites selected as being likely contaminat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
85
4
4

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 121 publications
(105 citation statements)
references
References 63 publications
10
85
4
4
Order By: Relevance
“…However, cleaning and disinfection operations may be effective only against the immediate risk. Yet incidents where L. monocytogenes cells remain on surfaces, despite multiple cleaning and disinfection procedures, have been frequently reported (15,47); such L. monocytogenes strains are called persistent. It is of some importance to remember that the aging of biofilms, since it causes an increased resistance to disinfectants (10), is likely to be a factor in contributing to persistence.…”
Section: Discussionmentioning
confidence: 99%
“…However, cleaning and disinfection operations may be effective only against the immediate risk. Yet incidents where L. monocytogenes cells remain on surfaces, despite multiple cleaning and disinfection procedures, have been frequently reported (15,47); such L. monocytogenes strains are called persistent. It is of some importance to remember that the aging of biofilms, since it causes an increased resistance to disinfectants (10), is likely to be a factor in contributing to persistence.…”
Section: Discussionmentioning
confidence: 99%
“…Floors and floor drains, areas previously described as sources of L. monocytogenes in food plant environments (34), were also included. Samples were collected using a Bacti-Sponge kit (Hardy Diagnostics, Santa Maria, CA) moistened with 10 ml of neutralizing buffer (Difco; BD Diagnostics, Sparks, MD) (19,33). For the milking equipment, a sponge was used to wipe the inner surface of the selected site.…”
Section: Methodsmentioning
confidence: 99%
“…Molecular subtyping of strains from raw fish, processing environments, and packed products has suggested that contamination during processing rather than contamination directly from raw fish is the principal cause of product contamination (1,9,23,24). The production process for cold-smoked salmon and other coldsmoked fish does not include a listeriacidal step, and only a better understanding of the sources and contamination routes of L. monocytogenes can specifically reduce the contamination of the product.…”
mentioning
confidence: 99%